Community participation in tourism development at Tanjung Setumu Beach, Dompak Island, Tanjungpinang City - Eriyanto, Eriyanto; Haidawati, Haidawati; Ulfah, Fitria (Politeknik Negeri Sambas, 2024)
Tourism is one of the important sectors in regional development because it is able to make a significant contribution to regional income. One of the tourism locations in Tanjungpinang city is Tanjung Setumu Beach on Dompak Island which occupies a strategic position close to the urban center, offers beautiful scenery, and is an attractive tourist destination. Thus, Tanjung Setumu Beach can improve the community's economy, open up employment and business opportunities, and contribute to regional income, especially through tourism management that involves direct community participation. Active participation from the community plays a very important role in supporting the development of tourism, especially community-based development, considering that successful development requires participation from various parties. The purpose of this study was to determine the level of community participation in tourism development at Tanjung Setumu Beach. The research was conducted in May-June 2023 with a quantitative descriptive approach using Likert Scale analysis. Based on the research results, the level of community participation in tourism management at Tanjung Setumu Beach, according to the score results, reached a good category on several indicators, such as providing labor, ideas, material contributions, and promotions for the purpose of developing tourist attractions.